A review on conceptual and practical oil and gas reservoir monitoring methods - Djuraev, U. (Elsevier B.V., 2017)
Reservoir monitoring is one of the key factors in the management of oil and gas resources. In particular, the evaluation of the Enhanced Oil Recovery (EOR) method through reservoir monitoring is crucial in EOR processes, where various fluids are injected into a reservoir to improve oil recovery. Reservoir monitoring methods enable engineers to conduct either direct or indirect surveillance to gather the required data. Depending on the objective of the monitoring program, a combination of two or more methods may need to be employed. However, in most cases, decisions are made based on the accessibility of the technology and the subsequent economic consideration. Therefore, selecting the most appropriate monitoring technique that would provide adequate data to meet the objective of the surveillance is critical with respect to EOR processes. The paper examines reservoir monitoring through a review of proposed, developed and implemented methods and techniques to enhance reservoir surveillance practices. Several methods, which range from well-established methods that are based on geophysical logging to emerging techniques that are derived from other fields of science and technology, are discussed. This review paper should serve as a reference to practicing engineers and researchers who aspire to improve the existing methods or develop new techniques. This review is divided into six sections based on the underlying principles of the monitoring methods. Real field application experiences are also included. At present, some of the methods that are discussed in the last section are mostly theoretical. However, these techniques may become routine with the advent of new technology and further research. © 2017 Elsevier B.V.